EDUCATION QUALITY MANAGEMENT AS THE DEVELOPMENT OF QUALITY STANDARDS OF HUMAN RESOURCES (SDM) TEACHERS IN MAN 2 MALANG CITY - Sukrisna, Chandra; Afifulloh, Mohammad; Muslim, Mohammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Education is a crucial human right for the progress of a nation, especially in the era of globalization. In Indonesia, the quality of education still faces various challenges, one of which is the role of professional and competent teachers in improving the quality of education. This study aims to explore education quality management as a strategic tool for teacher human resource development at MAN 2 Malang City. The research method used is a case study with data collection techniques through participatory observation, interviews, and documentation. The results showed that the quality standards of teachers at MAN 2 Malang City include a minimum of S1 education that is linear with the field of study taught and has educator certification. In addition, teachers are required to have religious skills that are applied in all subjects. Quality management at MAN 2 Malang City is implemented through careful planning, teacher competency tests, and training programs to improve teachers' pedagogical, social, professional, and personality qualities. The findings emphasize the importance of quality management in teachers' professional development to achieve quality education in Indonesia.